Climate Change in the Mediterranean over the Last Five Hundred Years - Camuffo, Dario (2012)
Global Warming (GW) is expected to affect the Mediterranean area with three major challenges, i.e. increase in temperature, decrease in precipitation and sea level rise that will likely submerge the coastal areas, including Venice. Aim of this Chapter is to discuss the expected changes under the light of long-term observations. Documentary proxies and instrumental readings in Portugal, Spain, France and Italy have been recovered and analysed. These observations cover the last five centuries from the Little Ice Age (LIA) to the present-day GW. This Chapter is based on documentary proxies and instrumental series collected over the Mediterranean area, i.e. Portugal, Spain, France and Italy within the EU funded ADVICE, IMPROVE, MILLENNIUM, and Climate for Culture projects. A huge effort was made to seek for written sources and original logs with early and less recent instrumental readings. The next steps were to recover, correct, adjust to modern standards, homogenize and analyse the earliest data and most of the longest European series. The detailed study of the history of the series (e.g. instrument type, calibration, observational methodology, sampling time, exposure, location) and the recovery of any related metadata were fundamental to apply and perform the due corrections to the series.